2008
DOI: 10.2337/dc08-0167
|View full text |Cite
|
Sign up to set email alerts
|

Is the Combination of Sulfonylureas and Metformin Associated With an Increased Risk of Cardiovascular Disease or All-Cause Mortality?

Abstract: OBJECTIVE -Observational studies assessing the association of combination therapy of metformin and sulfonylurea on all-cause and/or cardiovascular mortality in type 2 diabetes have shown conflicting results. We therefore evaluated the effects of combination therapy of sulfonylureas and metformin on the risk of all-cause mortality and cardiovascular disease (CVD) among people with type 2 diabetes. RESEARCH DESIGN AND METHODS-A MEDLINE search (January 1966 -July 2007) was conducted to identify observational stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
143
0
8

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 206 publications
(153 citation statements)
references
References 23 publications
2
143
0
8
Order By: Relevance
“…It cannot be concluded from the literature whether combination therapy with metformin and SU has harmful effects, as indicated by the UKPDS (13,(25)(26)(27). At present, the international guidelines recommend combination therapy when monotherapy fails (4).…”
Section: Oral Hypoglycaemic Agentsmentioning
confidence: 79%
See 1 more Smart Citation
“…It cannot be concluded from the literature whether combination therapy with metformin and SU has harmful effects, as indicated by the UKPDS (13,(25)(26)(27). At present, the international guidelines recommend combination therapy when monotherapy fails (4).…”
Section: Oral Hypoglycaemic Agentsmentioning
confidence: 79%
“…A recently published meta-analysis indicates an increased frequency of CVD by combined intervention with metformin and insulin secretagogues compared with diet or monotherapy (27).…”
Section: Metforminmentioning
confidence: 99%
“…Meta-analyses critical of rosiglitazone are mentioned repeatedly, while analyses reporting no increase in cardiovascular ischaemic risk with rosiglitazone versus other established glucose-lowering medications are overlooked (such as those performed by Lago et al [5] and the US Food and Drug Administration [FDA] [6]). A metaanalysis [7] that reported a statistically significant increase in a composite endpoint of cardiovascular hospitalisation or mortality with the combination of sulfonylureas and metformin-a tier 1 recommended option-is not mentioned in the consensus statement.…”
Section: Fda Food and Drug Administrationmentioning
confidence: 99%
“…Meta-analyses critical of rosiglitazone are mentioned repeatedly, while analyses reporting no increase in cardiovascular ischaemic risk with rosiglitazone versus other established glucose-lowering medications are overlooked (such as those performed by Lago et al [5] and the US Food and Drug Administration [FDA] [6]). A metaanalysis [7] that reported a statistically significant increase in a composite endpoint of cardiovascular hospitalisation or mortality with the combination of sulfonylureas and metformin-a tier 1 recommended option-is not mentioned in the consensus statement.The authors of the consensus statement write that 'the overarching principle in selecting a particular intervention will be its ability to achieve and maintain glycaemic goals' [1]. Rosiglitazone has been shown to provide glycaemic control for up to 5 years-significantly longer than the most commonly used oral glucose-lowering medications, sulfonylurea and metformin [2].…”
mentioning
confidence: 99%
“…27 In support of this, a meta-analysis of observational studies reported an increased risk of cardiovascular hospitalisation and mortality with the combination of metformin plus a sulphonylurea. 79 This presents a potential dilemma when considering the expansion of metformin use in CKD: the improved renal outcomes observed in the ADVANCE trial were achieved with a largely sulphonyureadriven protocol and so combination therapy could be argued to be the most evidence-based approach in this population. 16 However, despite the combination of metformin and a sulphonylurea being more frequent in the intensive control group of this study, an increase in mortality was not observed.…”
Section: A Lack Of Evidence For Metformin In Ckdmentioning
confidence: 99%